Focal hyperintensity in the dorsal brain stem of patients with cerebellopontine angle tumor: A high-resolution 3 T MRI study - Yamamoto, Hirotaka (Sci Rep, 2018)
Focal hyperintensity (FHI) in the dorsal brain stem on T2-weighted images of patients with cerebellopontine angle (CPA) tumor was thought to indicate degeneration of the vestibular nucleus and to be specific to vestibular schwannoma. The purpose of this study was to evaluate FHI by using high-resolution 3 Tesla magnetic resonance imaging (3 T MRI) and the relation to clinical characteristics. We retrospectively reviewed the clinical data and MRI of 45 patients with CPA tumors (34 vestibular schwannomas and 11 other tumors). FHI in the dorsal brain stem was found in 25 (55.6%) patients (20 vestibular schwannomas and 5 other tumors). For the vestibular schwannomas, the factors contributing to positive FHI were age (p = 0.025), max CPA (p =  < 0.001), hearing ability (P = 0.005), and canal paresis (p =  < 0.001) in the univariate analysis. Multivariate regression analysis showed that max CPA (p = 0.029) was a significant factor of positive FHI. In other CPA tumors, these factors were not significant predictors. With the use of 3 T MRI, FHI was observed more frequently than previously reported. Our results suggest that FHI is not a specific indicator of vestibular schwannoma and is related to not only vestibular function but also other factors.